A Critical Review Of The Use Of Social Media As A Medium For Arabic Language Learning - M Al Widad Ramadhan; Bayu Noval Azhari; Ahmad Nur Mizan (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2026)
This study critically examines the use of social media for Arabic language learning in higher education, highlighting the low motivation as well as the speaking and writing skills of students due to conventional approaches. Using a descriptive qualitative method involving 45 fourth-semester students of the Arabic Language Education study program at UIN Raden Intan Lampung, data were obtained through observation, interviews, analysis of social media posts, and open questionnaires. The results show that YouTube, Instagram, and WhatsApp have great potential as informal learning environments because they provide authentic language input, social interaction, and flexible access, although their use remains sporadic and not systematically integrated into the curriculum. The effectiveness of social media is largely determined by the educator's role as a facilitator, the type of content, and the frequency of meaningful interaction. This study concludes that social media is not merely a technical tool, but a new learning ecology that requires careful pedagogical design, with practical implications including the need to develop a social media-based blended learning model and to enhance digital literacy for both lecturers and students.